Effect of bias on the perception of two simultaneously presented ambiguous figures - Intaitė, M.; Šoliūnas, A.; Gurčinienė, O.; Rukšėnas, O. (Psichologija, 2013)
Ambiguous figures are pictures that reverse their appearance during prolonged viewing and can be perceived in two (or more) available interpretations. Explanations for this phenomenon favour either early bottom-up processes or higher-level top-down processes. This study aimed to investigate the perception of simultaneously presented neutral and biased (i.e. with a slight modification towards one or another of the available interpretations) ambiguous figures. Our results have indicated that observers tend to perceive two adjacent identical figures as reversing simultaneously, and the same percepts dominated both in the reversal rate and the duration of perception. In the case of biased and neutral figures presented in pairs, modifications of interpretation either increased or decreased the frequency of a biased percept. The results show that both bottom-up and top-down perceptual processes influence the perception of ambiguous figures.
Keywords: ambiguous figure; adaptation; multiple-figure presentation; bias; bias visual perception